344 Variation of tuck jump assessment kinetics in female athletes. (3rd March 2020) - Kember, Lucy; Moore, Isabel; Lloyd, Rhodri
Abstract : Background: The tuck jump assessment (TJA) is a criteria-based, clinician-friendly screening tool designed to identify neuromuscular deficits associated with anterior cruciate ligament (ACL) injury risk. However, caution must be applied when solely interpreting the composite scores due to high-within subject variation in individual criteria. Notably, the variation in kinetic characteristics of the TJA have yet to be reported. Objective: The aim of this study was to identify the difference and variation in kinetics during the TJA in female athletes. Design: Descriptive study. Setting: Laboratory. Patients (or Participants): Fifteen recreational female athletes (age 23.67±5.43 yr; height 1.69±0.9 m; body mass 70.6±11.7 kg). Interventions (or assessment of risk factors): A single trial of repeated tuck jumps were performed on a ground fixed force plate recording at 1000Hz for ten seconds. The first 12 tuck jumps were used for analysis and divided into three blocks of four contacts (B1, B2 and B3). Coefficient of variation (CV) within a block and differences between blocks were calculated for vertical ground reaction force (vGRF), displacement and leg stiffness. Main outcome measurements: vGRF (N), displacement (m) and leg stiffness (N/m). Results: There was no difference between each phase of the TJA for vGRF (B1: 3756±372 ; B2: 3827±282 B3: 3949±325), displacement (B1: 0.15±0.02; B2: 0.15±0.01; B3: 0.14±0.01), or leg stiffness (B1: 25.39±4.75; B2: 26.78±3.85; B3: 28.61±3.55). Tuck jumps in B2 demonstrated the lowest variability for vGRF (B1: CV=10.21%; B2: CV=7.79%; B3: CV=8.37%) whilst the last four tuck jumps had the lowest variability for displacement (B1: CV=10.38%; B2: CV=9.21%; B3: CV=6.68%) and leg stiffness (B1: CV=18.69%; B2: CV=15.14%; B3: CV=12.21%). Conclusions: The findings show that whilst each phase presented similar means, the smallest variability was observed in the final 8–12 tuck jumps. It is therefore recommended that this block within the TJA should be the focus for practitioners and repeated measures studies.